Analisis Kinerja Keuangan pada PT Sariguna Primatirta Tbk - Wedia Hastuti (Syntax Corporation Indonesia, 2024)
The purpose of this studyis to analyze the financial performance of PT Sariguna Primatirta Tbk tahun 2020 – 2022, in terms of the liquidity ratio, solvibility ratio, activity ratio and profitability ratio. Analysis ratio’s used for analyzing on this research. Based on the analysis of the liquidity ratio, using the current ratio, cash ratio and the quick ratio, the financial performance of PT Sariguna Primatirta Tbk tahun, it wasn’t good, because the company has a tendency to not cover its current liabilities on current assets, cash and bank’s saving and current assets regardless on inventories’ values. Then, based on the results of the solvency ratio analysis, seen from the debt to asset ratio and debt to equity ratio, it shows that the company's ability to pay off its debts, both short term and long term are still in good condition. This shows that the company's performance is quite good. From the results of the analysis using the activity ratio, working capital turnover shows that the company's working capital turnover in generating sales is still in good condition. Meanwhile, for total asset turnover, the company's ability to turnover total assets is ins’t good or unstable condition. Based on the results of profitability ratio analysis using net profit margin, return on equity and return on investment, there is instability, for return on equity and return on investment, meaning that the company's ability to generate net profits from its capital and assets is ins’t good or less stable. Meanwhile, the net profit margin results show that the company's ability to generate net profits from sales is still good.